Characterisation of Pinotage Wine During Maturation on Different Oak Products - de Beer, D.; Joubert, E.; Marais, J.; du Toit, W.; Fouché, B.; Manley, M. (South African Journal of Enology and Viticulture, 2016)
The effect of oak contact on the phenolic composition, total antioxidant capacity (TAC) and colour of Pinotage wines was investigated during maturation. Oak maturation included traditional treatments, such as new, second-fill and third-fill barrels, as well as alternative treatments (oak chips, staves, extract and dust) applied in old barrels over a period of 28 weeks. Oak maturation using traditional and alternative treatments improved the objective colour of Pinotage wine by decreasing the L* value. Losses in TAC caused by decreased concentrations of monomeric phenolic compounds (most anthocyanins, flavan-3-ols, flavonols and hydroxycinnamic acids) during oak maturation were negated by increased concentrations of gallic acid and the formation of new oligomeric and polymeric pigments. Wine maturation in stainless steel containers also resulted in a decrease in anthocyanin content. The decrease in phenolic acid content for wines matured in stainless steel was less pronounced, while their flavan-3-ol content remained stable. The new-barrel treatment had the most pronounced effect on all parameters. Oak maturation can be used for the production of Pinotage wine when the retention of TAC is a high priority.